A content-addressable memory structure using novel majority gate with 5-input in quantum-dot cellular automata - H. Majeed, Ali; Zainal, Mohd Shamian; Alkaldy, Esam; Md Nor, Danial (UTHM Publishing, 2020)
Quantum-dot Cellular Automata (QCA) technology is one of the most important new nanotechnologies and is a suitable replacement for CMOS circuits. Majority gate and Inverter are the primary building blocks in QCA circuits. Content Addressable Memory (CAM) is a type of memory used in applications that require high speed. In this paper, a novel five input majority gate is introduced. This gate is simulated with QCADesigner tool and compared with previous same structures. Then, the proposed gate used to design a CAM cell in a single layer after deriving the minority gate from the proposed majority gate. The proposed CAM cell has a simple and robust structure and does not require wire crossover, also it reduces circuit complexity by 7% in term of cell count compared to existing structures.